ANALISIS KEMITRAAN DAN PENGARUHNYA TERHADAP PENDAPATAN PETANI JAGUNG MADURA-3 - Abdul Azis Jakfar; Norita Vibriyanto (AGROINTEK, 2021)
The aims of this study are: 1) describe of implementation partnership on the Madura-3 corn in Bangkalan Regency. 2) analyze the income impact of partnerships on Madura-3 corn farmers in Bangkalan Regency. Type of this research are survey research and literature review. The data that used in this study are primary and secondary data. Primary data were obtained from direct sources of research objects, secondary data were obtained from literature studies, which consisted of research journals, reference books, data from related institutions, and other sources of reading material. This reseach use descriptive method that is describing the facts are occur at the study site. Results of this studies, there is advantage obtained from the partnership such as market guarantees so that income of Madura 3 corn farmers is higher than others corn farmers, pattern of partnership is the agribusiness operational cooperation.